Clinical Practice Recommendations for Continuation and Maintenance Electroconvulsive Therapy for Depression: Outcomes From a Review of the Evidence and a Consensus Workshop Held in Australia in May 2017. Issue 1 (March 2019) - Gill, Shane P.; Kellner, Charles H.
Abstract : Objectives: Continuation or maintenance electroconvulsive therapy (ECT) is often provided as a strategy for post-ECT relapse prevention. However, the evidence has been insufficient until recently to produce clear consensus on what best practice maintenance ECT (mECT) should be like in a real world ECT clinical service. The aims of this article are to help fill this gap and to provide a comprehensive set of practical, clinically-based recommendations for ECT clinicians and services. Methods: A workshop was held at the Royal Australian and New Zealand College of Psychiatry Congress in Adelaide on April 30, 2017. This workshop was hosted by the authors. After a presentation on the state of the evidence, the 30 participants were asked to work in small groups to develop consensus recommendations on different aspects of mECT. These were then collated into one comprehensive set of clinical recommendations for the practice of mECT. Results: These best practice recommendations are set out below. Conclusions: These recommendations will assist ECT services and clinicians to provide best practice mECT according to currently available evidence.